Tantangan dan Peluang Administrasi Publik dalam Membangun Kapasitas Pemerintah Daerah - Amanda Iqlimah; Izah Meitara; M. Dio Novaldy; Syaparman Syaparman (Lembaga Pengkajian Dan Pengembangan Sumberdaya Pembangunan (lppsp), 2024)
Since the implementation of decentralization policies through Law No. 22 of 1999 and Law No. 23 of 2014, local governments have been granted broader authority in managing governance affairs. However, the implementation of decentralization faces challenges, particularly the low capacity of local governments in carrying out their functions optimally. This study uses a descriptive qualitative method to explore the challenges and opportunities in enhancing local government capacity. Data was collected through interviews with local government officials, public administration experts, and community leaders, as well as through literature studies. The findings indicate that the use of digital technology through e-government plays a significant role in improving local government capacity by simplifying bureaucracy, increasing transparency, and accelerating data-driven decision-making. However, challenges such as limited technological infrastructure and low digital literacy among civil servants remain major barriers. To address these issues, investments in digital infrastructure, digital literacy training for civil servants, and policies supporting digital transformation are needed. With these strategies, local governments can improve efficiency, transparency, and accountability in public services, while maximizing resources for sustainable development.